Dinamika Perilaku Siswa Madrasah Aliyah Di Jakarta - Marsyah Qoriatul Rizky; Ni’mah Fauziah; Kaisyah Maulydia; Alfiansyah Alfiansyah; Ummah Karimah (LP3M IAI Al Urwatul Wutsqo Jombang, 2025)
The dynamics of student behavior in this study are a process of how the development of student behavior is influenced by various factors, including the family environment, the role of teachers, patterns of social interaction at school, and exposure to the development of digital technology. The dynamics of student behavior referred to in this study are discipline. Discipline in this study is the ability to control and direct one's behavior in the school environment, so that a sense of responsibility and self-reliance arises, which makes the student learning process run smoothly. The discipline referred to in this study includes discipline in learning, obeying school rules and regulations, and discipline towards time utilization. This research uses a research method with qualitative field research method. The data were collected through interviews and observations. Data analysis through data triangulation. The results showed that the implementation of learning the values of discipline in Madrasah Aliyah is as follows: (1) Teachers often find students who are less enthusiastic during the last hour. (2) The school will take firm action if it finds students who commit crimes. (3) The backgrounds of students are different and come from outside the area. Because student discipline is a person's obedience and compliance with the rules, rules and regulations that apply.